The Revised Statutes of The State of Maine, Passed January 25, 1871 at 293, § 24 (1871) - (:unkn) unknown (General Publisher, 1871)
Allowed municipal officers to regulate storage or transportation of gun powder. Also allowed municipal officers to enter any building with a search warrant to find concealed articles contrary to regulations..
--
Keywords: GUN POWDER STORAGE